Health-related quality of life with long-term retention of the PROSthesis of Antibiotic Loaded Acrylic Cement system following infection resolution in low demand patients - Beaupre, Lauren A; Stampe, Kyle; Masson, Edward; O’Connor, Gregory; Clark, Marcia; Joffe, A Mark; Boychuk, Lesia R; Lavoie, Guy (Journal of orthopaedic surgery (Hong Kong), 2017)
Background: The study purpose was to (1) evaluate health-related quality of life (HRQL) with the PROSthesis of Antibiotic Loaded Acrylic Cement (PROSTALAC) in situ for infected total hip arthroplasty (THA), (2) determine infection resolution, and (3) compare subjects who underwent second stage surgery with those who retained the PROSTALAC on a longer term basis. Methods: Demographics, physical demand level, and comorbidities were recorded prospectively in 29 subjects followed to at least 24 months after initial PROSTALAC insertion. HRQL was evaluated using the Western Ontario McMaster Osteoarthritis Index (WOMAC) and RAND 36-Item Health Survey. Infection resolution was determined using a pre-specified clinical definition. Results: Twenty-five of 29 (86%) subjects’ infections resolved. Three subjects died, of whom two had resolved infections. For survivors, 22/26 (85%) completed HRQL evaluations. After PROSTALAC insertion, pain and function improved within 3–6 months and was retained at 24 months. Of those followed to 24 months, 7/22 (32%) subjects underwent second stage surgery. They were higher physical demand subjects (p = 0.03) than those not undergoing second stage surgery. We found no difference in WOMAC scores at 24 months between those who underwent second stage surgery and those who retained the PROSTALAC (p > 0.32). Discussion: The PROSTALAC system for THA appears to allow acceptable HRQL while in situ for at least 2 years in low physical demand patients. Subjects with higher physical demand levels are more likely to undergo second stage surgery. Conclusion: Further evaluation is required to determine whether longer term PROSTALAC retention may be appropriate for specific patient groups.